Comparative analysis of oncolytic potential of vesicular stomatitis virus serotypes Indiana and New Jersey in cancer cell lines - A. S. Isaeva; N. O. Porozova; E. Idota; S. I. Volodina; A. N. Lukashev; A. S. Malogolovkin (Сеченовский вестник)
Aim. Compare the lytic efficiency and the kinetics of accumulation of vesicular stomatitis virus serotypes Indiana (VSV-IND) and New Jersey (VSV-NJ) on cell lines of mouse melanoma B16F10, human hepatocellular carcinoma HepG2 and human mammary adenocarcinoma MCF7.Materials and methods. The viability of mouse melanoma B16F10, human hepatocellular carcinoma HepG2 and human mammary adenocarcinoma MCF7 cell lines infected with VSV-IND and VSV-NJ viruses at different multiplicity of infection (10 MOI; 1 MOI; 0.1 MOI) was assessed after 24, 48 and 72 hours, and the half maximal inhibitory concentration (IC50) values were measured using the methyl tetrazolium test. The relationship with virus accumulation in cell culture was determined using reverse transcription – quantitative polymerase chain reaction; 50% tissue culture infectious dose (TCID50) of VSV-IND and VSV-NJ for B16F10, HepG2, MCF7 were calculated using the Reed-Muench method.Results. The most susceptible cell line for both viruses was B16F10: cell viability 72 hours after infection at 10 MOI was only 10.4% and 5.7% for VSV-IND and VSV-NJ, respectively. HepG2 cell viability at 72 hours post-infection at 10 MOI was 10.8% and 9.8% for VSV-IND and VSV-NJ, and for MCF7 adenocarcinoma it was 46.6% and 36.2%, respectively. Moreover, only in the B16F10 culture was a positive statistically significant correlation of medium strength established between the inhibition of cell viability and the accumulation of viral RNA: for VSV-IND r = 0.601 (p < 0.05); for VSV-NJ r = 0.668 (p < 0.05). HepG2 and MCF7 showed no significant correlation.Conclusion. The research results indicate the potential of using oncolytic viruses of the VSV-IND and VSV-NJ as a platform for the development of new recombinant viruses for virotherapy of solid tumors in combination with other types of treatment.